Does Livelihood and Asset Diversification Contribute to Pastoralist Resilience?: the Case of Il Chamus, Baringo County, Kenya, 1980-2018. (1st October 2021) - Little, Peter D.
In studies of pastoralism, the concept of resilience has normally been applied to the analyses of post-shock recoveries ('bounce backs') within an ecological framework and and limited time and spatial perspectives. When temporal and spatial parameters are relaxed to span multiple decades and geographies with widespread social changes and numerous shocks and recovery periods, understanding what resilience for pastoralists should look like is exceedingly complex and challenging. This article examines livelihood and asset diversification among Il Chamus of Baringo County, Kenya over a 35+ year period (1980-2018) in the context of significant changes. It suggests that 'successful resilience' among pastoralists involves much more than the continuity of a pastoralist livelihood in a particular place. By addressing diversification trends among households both in towns and rural spaces, the study shows that both better-off and poor households pursue non-pastoral strategies and assets, and that livestock remains an important real and symbolic form of capital even for those who work in towns. Finally, the article concludes that studies of pastoralist resilience should consider long-term continuities and changes associated with market expansion and the strengthening of rural-town linkages, in order to understand how pastoral livelihoods evolve not just in response to short-term shocks but also to challenges and opportunities that wider socio-economic changes present.